Extra-Nodal Follicular Dendritic Cell Sarcoma with Unusual Morphological Features and PDL1 Expression - Ranade, Manali; Shah, Aekta; Yadav, Subhash; Menon, Santosh; Gupta, Sudeep (Indian Journal of Medical and Paediatric Oncology, 2022)
Follicular dendritic cell (FDC) sarcoma, a rare tumor of FDCs, poses a diagnostic challenge due to its myriad morphologic and architectural patterns. We present a unique case of extra-nodal FDC sarcoma occurring in a 28-year-old gentleman who presented with multiple pelvic, peritoneal and retroperitoneal soft tissue, and axial skeletal lesions. The tumor was composed of islands and trabeculae of epithelioid cells with interspersed lymphocytes against a background of abundant myxoid matrix. On immunohistochemistry, in addition to the CD21, the tumor was positive for GATA3, inhibin, and programmed death-ligand 1 (PDL1), which have been rarely reported previously in FDC sarcoma. The patient underwent surgical excision of the tumor and was later offered immunotherapy. He has been disease-free for 2 years following immunotherapy. Our case highlights the potential role of immune checkpoint inhibitors in treating FDC sarcoma, which show immuno-expression of PDL1.
Keywords: follicular dendritic cell sarcoma; PDL1; immunotherapy